2021
DOI: 10.1021/acs.chemmater.1c03489
|View full text |Cite
|
Sign up to set email alerts
|

Stabilities of Isomers of Phosphorus on Transition Metal Substrates

Abstract: Great efforts have been dedicated to synthesizing phosphorene on transition metal surfaces, but there has been limited success until now. The strong interaction between phosphorus and the substrate may lead to many possible highly stable isomers of phosphorus, making the synthesis of phosphorene difficult. Here, we studied whether functionalizing transition metal surfaces by different phosphorous isomers can assist the epitaxial growth of blue phosphorene. Using density functional theory, we systematically exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…According to these results, armchair chains can be synthesized at low P coverage; pentamers can be synthesized at medium P coveragewhich have been observed experimentallyand blue phosphorene is produced at high P coverage. Although the BLP, modified BLP, surface phosphide, and Ag-P hybrid have been explored in a previous study, here, we identified two additional structures with much better stability in comparison with four abovementioned structures.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…According to these results, armchair chains can be synthesized at low P coverage; pentamers can be synthesized at medium P coveragewhich have been observed experimentallyand blue phosphorene is produced at high P coverage. Although the BLP, modified BLP, surface phosphide, and Ag-P hybrid have been explored in a previous study, here, we identified two additional structures with much better stability in comparison with four abovementioned structures.…”
Section: Resultsmentioning
confidence: 75%
“…To check whether phosphorus pentamers are stable on other metal surfaces, we calculated the stabilities of a single P atom, an armchair chain, a pentamer, and blue phosphorene and compared them with the most stable metal-P structures reported recently 33 on Au(111), Cu(111), Co(0001), Ni(111), and Pt(111) substrates. The formation energies of pentamers at different coverages on the five substrates are shown in Figure S3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, a modified BlueP structure on a (4 × 4) Ag(111) supercell was constructed with lower atomic density, where the left and right half unit cells are in mirror symmetry (Figure 3f). 34 In comparison to the perfect BlueP, the stability is reduced in the modified BlueP with different bond angles. As summarized in Table 2, the most favorable bonding angle in the buckling configurations is 95°(close to that of BP 44 ) corresponding to the perfect BlueP structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In general, tetrahedral P 4 molecule is the most stable P allotrope in the gas phase and can be generated by the thermal evaporation of different bulk precursors, including black and red P. ,, However, the stability of the P molecules could change significantly when they are attached on surfaces, , and transformation into various configurations could occur during the nucleation, aggregation, and growth processes. ,, Thus, it is important to understand the stability and evolution of different P allotropes upon adsorption, including 0D clusters, 1D chains and nanoribbons, and 2D single-layered films. Various metal substrates have been used as substrates for the growth of P, including Au, Ag, Cu, and Pt.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation